Pengembangan Bahan Ajar Dengan Menggunakan Pendekatan Saintifik Untuk Meningkatkan Kreatifitas Siswa Di Kelas X Sekolah Menengah Atas - Fitri Agustina; Jalilah Azizah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2019)
his study aims to produce a teaching material based on the scientific approach that is valid, practical, and effective and can increase creativity in biology learning in high school class X. The method used in this development is the 4-D Model (Four D Model) development model, which consists of four stages are: define, design, develop, and spread (disseminate). Development research is a research method for developing products and improving products. The defining stage is carried out by the determination of learning conditions by analyzing competency standards and boundaries of the subject matter that will be taught by the teacher based on the 2013 curriculum content standards. The planning stage for the preparation of instruments needed in this study and the design of prototype teaching materials. Development stage 1) expert appraisal followed by revision, and 2) development trials limited to students (developmental testing). Stage of dissemination (disseminate) by publishing teaching material that has been developed in the form of a journal. The ability of students has increased, this can be seen from the percentage of classical completeness of students in the first trial of 36%, and the percentage of classical completeness of students in the second trial was 83%. In other words an increase in the biological representation of students in the ecosystem material from the first trial to the second trial increased. Keywords: Development, Teaching Materials, Creativity